Gun-Related Crime in Detroit, Michigan: Exploring the Spatial Context of Licensed Firearm Availability and Neighborhood Characteristics. (3rd April 2019) - Xu, Yanqing; Owusu-Agyemang, Samuel
Abstract: The linkage between firearms and violent crime has been documented in several criminological research efforts, with different conclusions. This study explores the relationship between gun availability and gun-related violent crimes, using the city of Detroit, Michigan, as a case study. Based on the primary role of federal firearm licensees (FFLs) as a spigot for the flow of firearms into communities, spatial accessibility to FFL locations is used as a measure of gun availability. Global regression models are used to investigate the association between gun-related crime rates and spatial accessibility to FFL locations. Geographically weighted regression (GWR) is also employed to assess such spatially varying accessibility across the study area. In the global models, gun availability and selected population variables explained up to 46 percent of the variation in crime rates. The GWR model explained 59 percent of the variation in crime rates. The analysis shows a global significant positive effect of gun availability on gun-related crime rates, with strong spatial variability across the study area. The results suggest a significant linkage between gun-crime rates and spatial accessibility to FFL in the study area. Based on the findings, the location and activities of FFL dealers might be a contributing factor to the rates of gun-related crimes.